Assessing the Impacts of Climate Change on the Quantity and Quality of Agricultural Runoff (Case Study: Golgol River Basin)†. (8th January 2018) - Moshtaghi, Bahman; Niksokhan, Mohammad Hossein; Ghazban, Fereydoun; Dalilsafaee, Sepehr
Abstract: The effects of climate change and global warming have become increasingly evident in recent years. Changes in climate may impact water availability, water needs for agriculture and agricultural runoff. The Golgol River Basin has been investigated to examine the effect of climate change. HadCM3 model output under the A2 emission scenario during the two periods of 2046–2065 and 2080–2099 is used to predict temperature and precipitation amount under climate change impact, while the LARS‐WG model is used for downscaling. SWAT was applied to simulate runoff, nitrate and organic nitrogen. The SWAT‐CUP and SUFI‐2 methods were used for calibration. Introducing downscaled results of AOGCM models into the hydrological model and assuming similar regional conditions including fertilizer and land use, the changes in runoff and pollutants in the future were also simulated. It was observed that during 2046–2065, the average monthly runoff, nitrate and organic nitrogen loads would decrease by 27, 18 and 13.5%. The 2080–2099 period when compared to the present shows that the average monthly runoff, nitrate and organic nitrogen loads would decrease by 45, 33 and 35%. So according to runoff quality degradation, management solutions must be found to reduce pollutants. Copyright © 2018 John Wiley & Sons, Ltd.